Stabilising financial markets: Lending and market making as a last resort - Willem H. Buiter; Stephen G. Cecchetti; Kathryn M. Dominguez; Antonio Sánchez Serrano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
This report looks backwards to the worldwide use of (enhanced) lender of last resort (LOLR) and market maker of last resort (MMLR) facilities during the global financial and the pandemic crises. It discusses how LOLR and MMLR facilities have worked; looking ahead, it considers what benefits and costs they could generate if authorities felt compelled to use them. Based on this analysis, the report presents a set of desirable attributes for an effective enhanced LOLR and MMLR and identifies two avenues for future macroprudential work. First, there is a strong need for an agreed taxonomy for determining which markets are systemic. And second, there is a need for a better understanding of how to structure facilities to mitigate moral hazard.
Keywords: 330; financial market supervision; central bank; lender of last resort; stockbroker; quantitative easing; Euro zone; Finanzmarktaufsicht; Zentralbank; Lender of Last Resort; Börsenmakler; Quantitative Lockerung; Welt; Eurozone